Analisis Faktor yang Mempengaruhi Perokok Beralih ke Produk Alternatif Tembakau (VAPE) menggunakan Metode K-Means Clustering - Azmi Musyaffa Fadhilah; M Iwan Wahyuddin; Deny Hidayatullah (KITA Institute, 2021)
This research was conducted based on the emergence of a trend in Indonesia, namely the use of alternative tobacco products (vape). It is known that the use of vape can make smokers reduce smoking activities or even make smokers quit smoking because of many factors to switch to vaping. The purpose of this study was to obtain the results of the analysis of factors that influence smokers to switch to alternative tobacco products (vape). This study uses the K-means method and uses the factors of age, income, duration of smoking, and time period of using vape as parameters. Data collection techniques are in the form of data collection by questionnaire. The subject of this research is the vape community that is part of the Facebook forum (JBDJ-Jual Beli Depok Jaksel).